Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve for [tex]\((f-g)(x)\)[/tex], we need to subtract [tex]\(g(x)\)[/tex] from [tex]\(f(x)\)[/tex].
Given the functions:
[tex]\[ f(x) = 3x^3 + 4x^2 - 6x - 7 \][/tex]
[tex]\[ g(x) = 2x - 4 \][/tex]
We can write the subtraction of [tex]\(g(x)\)[/tex] from [tex]\(f(x)\)[/tex] as follows:
[tex]\[ (f-g)(x) = f(x) - g(x) \][/tex]
Now, let's perform the subtraction step-by-step:
1. Write down [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] in their expanded forms:
[tex]\[ f(x) = 3x^3 + 4x^2 - 6x - 7 \][/tex]
[tex]\[ g(x) = 2x - 4 \][/tex]
2. Subtract [tex]\(g(x)\)[/tex] from [tex]\(f(x)\)[/tex]:
[tex]\[ (f-g)(x) = (3x^3 + 4x^2 - 6x - 7) - (2x - 4) \][/tex]
3. Distribute the negative sign across [tex]\(g(x)\)[/tex]:
[tex]\[ (f-g)(x) = 3x^3 + 4x^2 - 6x - 7 - 2x + 4 \][/tex]
4. Combine like terms:
[tex]\[ (f-g)(x) = 3x^3 + 4x^2 - 6x - 2x - 7 + 4 \][/tex]
[tex]\[ (f-g)(x) = 3x^3 + 4x^2 - 8x - 3 \][/tex]
So, the function [tex]\((f-g)(x)\)[/tex] is:
[tex]\[ (f-g)(x) = 3x^3 + 4x^2 - 8x - 3 \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{D. \ (f-g)(x) = 3x^3 + 4x^2 - 8x - 3} \][/tex]
Given the functions:
[tex]\[ f(x) = 3x^3 + 4x^2 - 6x - 7 \][/tex]
[tex]\[ g(x) = 2x - 4 \][/tex]
We can write the subtraction of [tex]\(g(x)\)[/tex] from [tex]\(f(x)\)[/tex] as follows:
[tex]\[ (f-g)(x) = f(x) - g(x) \][/tex]
Now, let's perform the subtraction step-by-step:
1. Write down [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] in their expanded forms:
[tex]\[ f(x) = 3x^3 + 4x^2 - 6x - 7 \][/tex]
[tex]\[ g(x) = 2x - 4 \][/tex]
2. Subtract [tex]\(g(x)\)[/tex] from [tex]\(f(x)\)[/tex]:
[tex]\[ (f-g)(x) = (3x^3 + 4x^2 - 6x - 7) - (2x - 4) \][/tex]
3. Distribute the negative sign across [tex]\(g(x)\)[/tex]:
[tex]\[ (f-g)(x) = 3x^3 + 4x^2 - 6x - 7 - 2x + 4 \][/tex]
4. Combine like terms:
[tex]\[ (f-g)(x) = 3x^3 + 4x^2 - 6x - 2x - 7 + 4 \][/tex]
[tex]\[ (f-g)(x) = 3x^3 + 4x^2 - 8x - 3 \][/tex]
So, the function [tex]\((f-g)(x)\)[/tex] is:
[tex]\[ (f-g)(x) = 3x^3 + 4x^2 - 8x - 3 \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{D. \ (f-g)(x) = 3x^3 + 4x^2 - 8x - 3} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.